2013
DOI: 10.1007/s00775-013-0996-2
|View full text |Cite
|
Sign up to set email alerts
|

How are hydrogen bonds modified by metal binding?

Abstract: How are hydrogen bonds modified by metal binding?Husberg, Charlotte; Ryde, Ulf General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of private study or research.• You may not fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 66 publications
0
3
1
Order By: Relevance
“…This result contradicts recent QM calculations in the blue copper protein azurin, [31] which suggest a weaker sulfur-hydrogen bond in the oxidized state. The difference might be attributed to either an increased flexibility in the reduced protein (which is not the case, based on NMR studies [21]) or, more likely, to a lowered stability of the reduced protein, as reported in unfolding studies [32].…”
contrasting
confidence: 99%
“…This result contradicts recent QM calculations in the blue copper protein azurin, [31] which suggest a weaker sulfur-hydrogen bond in the oxidized state. The difference might be attributed to either an increased flexibility in the reduced protein (which is not the case, based on NMR studies [21]) or, more likely, to a lowered stability of the reduced protein, as reported in unfolding studies [32].…”
contrasting
confidence: 99%
“…Coordination of a water molecule to a metal ion greatly influences its hydrogen bonding. Analysis of crystal structures from the Cambridge Structural Database (CSD) and ab initio calculations show that the hydrogen bonding between coordinated and noncoordinated water molecules is much stronger than that between two noncoordinated waters . Similarly, the interaction of benzene with coordinated water is stronger than with noncoordinated water .…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of crystal structures from the Cambridge StructuralD atabase (CSD) and ab initio calculations show that the hydrogen bonding between coordinated and noncoordinated water molecules is much stronger than that between two noncoordinated waters. [9,10] Similarly, the interaction of benzene with coordinated water is stronger than with noncoordinated water. [11] These effectsare considera-bly increased when the metal complexes are charged, fore xample,[Zn(H 2 O) 6 ] 2 + versus [ZnCl 2 (H 2 O) 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bulk water becomes depleted in highly concentrated ionic solutions; therefore, the first hydration shells of cations and anions begin to overlap, thus placing the water molecule under simultaneous influence of both charges (positive and negative). Under these circumstances, alkali ons attract and localize the lone pairs of oxygen and strengthen the OÀH···X À Hb, constituting the cooperative effect of cations and anions M + ···OÀH···X À (in which M = Li, Na, K, Cs and X = F, Cl, Br, I), which was already demonstrated by high-level ab initio [19] and density functional theory [20] simulation studies, and is herein shown experimentally for the first time ( Figure 2). Therefore, ordering of alkali-perturbed solutions demonstrates the cooperative trend in which the more densely charged M + ion strengthens the M + ···OÀH···Cl À Hb, bringing them closer to WWHb (i.e.…”
Section: Raw Spectramentioning
confidence: 80%